(untitled) (Ius Novum, 2023)
The Act on the Support to Households in Bearing the Costs Associated with the Change in the Digital Terrestrial Television Broadcasting Standard was passed by the government on 24 February 2022, only to be amended after a month, on 23 March 2022, as it became necessary to clarify the issue of the circle of people entitled to receive State support, which is absolutely fundamental from the point of view of this Act. The paper will therefore attempt to determine the content of the normative set by interpreting the provisions of the said Act so that it takes into account all functional relationships of the standards under study and is based on all available sources of information. At the same time, when analysing statutory instruments, the author will reflect on their compliance with the principle of specificity of law, as inferred by the Constitutional Tribunal from the constitutional principle of rule of law.